Sterility of Ethyl Chloride Spray After Use in the Clinic. (March 2021) - Sandrowski, Kristin; Graham, Jack; Knott, Samantha; Hickok, Noreen; Fitzgerald, Keith; Beredjiklian, Pedro K.; Rivlin, Michael
Background: Ethyl chloride spray is used frequently in the outpatient setting as a local anesthetic for injections and aspirations with varying consensus about the sterility of the spray. We hypothesize that ethyl chloride spray remains sterile and would show no bacterial growth during routine clinical use.Methods: Thirteen ethyl chloride bottles were collected for testing. Two unopened bottles were used as controls. Eleven unopened bottles were placed in orthopedic clinics and recollected after varying duration of use. The final volume and duration of use were recorded. Each bottle was sprayed in a separate test tube and allowed to evaporate. Trypticase soy broth was added to each tube and incubated for 48 hours. Control test tubes with broth alone were prepared and incubated under the same conditions. Cultures were evaluated at 24 and 48 hours.Results: The mean duration of ethyl chloride bottle use prior to culturing was 26 days. The average volume used per day was 1.9 mL. Each ethyl chloride bottle had an initial volume of 103.5 mL. Using the average daily volume usage, an extrapolated lifespan of each bottle was estimated at 7.7 weeks. None of the samples showed bacterial or fungal growth at 24 or 48 hours.Conclusion: Ethyl chloride bottles used in the clinical settings showed no bacterial or fungal contamination through their shelf life and routine use. The duration and amount of use did not affect sterility. Although the antimicrobial activity of ethyl chloride spray on skin is debated, ethyl chloride itself remains sterile through clinical use.